Meaning Recognition Terms in Arabic Semantic Studies - Aathifah Al Farros; Ida Wijayanti; Agustiar Agustiar (Yayasan Adra Karima Hubbi, 2024)
Background. This research is motivated by the complexity of understanding meaning in linguistic contexts, especially in Arabic, which involves various semantic theories. Purpose. The purpose of the study is to examine theories of understanding meaning in Arabic semantics to provide a foundation for the effective and efficient use of language. Method. The method used is a literature study with data sources from scientific books and articles accessed online. Results. The results show that there are five main theories in understanding meaning in Arabic semantics: referential theory (al-nazhariyah al-isyariyah) which identifies meaning based on its references, ideological theory (al-nazhariyah al-thashawuriyah) which views language as a means of conveying ideas, behaviorist theory (al-nazhariyah al-sulukiyah) which studies meaning through the behavior of language users, contextual theory (al-nazhariyah al-siyaqiyah) which emphasizes the importance of context in expressing meaning, and the theory of the field of meaning (nazhariyah al-huqul al-dalaaliyah) which views vocabulary as part of an interconnected area or field. Conclusion. In conclusion, an understanding of these theories is important for exploring the complexity of meaning in the linguistic context of the Arabic language, so that it can support better use of the language.